Mechanisms of Congenital Myasthenia Caused by Three Mutations in the COLQ Gene - Luo, Xiaona; Wang, Chunmei; Lin, Longlong; Yuan, Fang; Wang, Simei; Wang, Yilin; Wang, Anqi; Wang, Chao; Wu, Shengnan; Lan, Xiaoping; Xu, Quanmei; Yin, Rongrong; et al. (Frontiers in Pediatrics, 2021)
The gene encoding collagen like tail subunit of asymmetric acetylcholinesterase (COLQ) is responsible for the transcription of three strands of collagen of acetylcholinesterase, which is attached to the endplate of neuromuscular junctions. Mutations in the COLQ gene are inherited in an autosomal-recessive manner and can lead to type V congenital myasthenia syndrome (CMS), which manifests as decreased muscle strength at birth or shortly after birth, respiratory failure, restricted eye movements, drooping of eyelids, and difficulty swallowing. Here we reported three variants within COLQ in two unrelated children with CMS. An intronic variant (c.393+1G>A) and a novel missense variant (p.Q381P) were identified as compound heterozygous in a 13-month-old boy, with the parents being carriers of each. An intragenic deletion including exons 14 and 15 was found in a homozygous state in a 12-year-old boy. We studied the relative expression of the COLQ and AChE gene in the probands’ families, performed three-dimensional protein structural analysis, and analyzed the conservation of the missense mutation c.1142A>C (p.Q381P). The splicing mutation c.393+1G>A was found to affect the normal splicing of COLQ exon 5, resulting in a 27-bp deletion. The missense mutation c.1142A>C (p.Q381P) was located in a conserved position in different species. We found that homozygous deletion of COLQ exons 14–15 resulted in a 241-bp deletion, which decreased the number of amino acids and caused a frameshift translation. COLQ expression was significantly lower in the probands than in the probands’ parents and siblings, while AChE expression was significantly higher. Moreover, the mutations were found to cause significant differences in the predicted three-dimensional structure of the protein. The splicing mutation c.393+1G>A, missense mutation c.1142A>C (p.Q381P), and COLQ exon 14–15 deletion could cause CMS.